2002
DOI: 10.1016/s0006-3495(02)75229-6
|View full text |Cite
|
Sign up to set email alerts
|

Troponin-Tropomyosin: An Allosteric Switch or a Steric Blocker?

Abstract: The interaction of myosin subfragment 1 (S1) with actin-tropomyosin-troponin (regulated actin) is highly nucleotide dependent. The binding of S1 or S1-ADP (but not S1-ATP nor N,N'-rho-phenylenedimaleimide-modified S1-ATP) to regulated actin activates ATP hydrolysis even in the absence of Ca(2+). Investigations with S1 and S1-ADP have led to the idea that some actin sites are directly blocked toward the binding of S1 either by tropomyosin or troponin. The blocked state is thought to occur only at ionic strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 54 publications
6
51
0
Order By: Relevance
“…Tobacman (54) invokes actin-actin communication that is propagated along the filament and is linked to the effect of Tm and S1 to the conformation of the actin monomer. The Smith et al (55,56) (57,58). In the work presented here, we do not measure any cooperativity parameter or provide data that further defines switching between regulatory states.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacman (54) invokes actin-actin communication that is propagated along the filament and is linked to the effect of Tm and S1 to the conformation of the actin monomer. The Smith et al (55,56) (57,58). In the work presented here, we do not measure any cooperativity parameter or provide data that further defines switching between regulatory states.…”
Section: Discussionmentioning
confidence: 99%
“…There are alternative regulatory mechanisms. Instead of directly regulating actin-myosin interaction by blocking or unblocking binding sites, the state of the thin filament may allosterically control the transition of crossbridges to force states [23,24,43,121]. To control the transition instead of the binding would be advantageous for muscles, especially for the myocardium, enabling a fast reversible relaxation that is not counteracted by the crossbridges formed during contraction.…”
Section: Cross-bridge Kinetics and Thin-filament Inactivation During mentioning
confidence: 99%
“…Unlike the switched off monomers, the switched on monomers are able to activate myosin ATPase, i.e. actin monomers may be in the so-called http ''active/inactive'' functional states ( [16] for a review, see [1]). Polarized fluorimetry has shown that in muscle fibers the switched on and switched off monomers differ in filament flexibility and orientation relative to the filament axis [13][14][15][17][18][19].…”
Section: Introductionmentioning
confidence: 99%